Effects of the species of crosslinking reagents on the structures and properties of biodegradable poly (butanediol sebacate ‐ butanediol terephthalate) copolyester. Issue 20 (7th January 2022) - Li, Zhimao; Li, Yingchun; He, Maoyong; Wang, Wensheng; Li, Jie
Abstract: In the present study, poly(butylene sebacate‐co‐terephthalate)s having different crosslinking reagents were synthesized with a random distribution by a two‐step esterification and one‐step polycondensation process. In detail, the using crosslinking agents were included trimethylolethane (TME), trimethylolpropane, tris(hydroxymethyl)aminoethane, glycerol (GL). Particularly, CS refers to a sample with no crosslinking agent added. The copolyester with TME was the least crystalline sample, and the melting peaks of all copolyesters corresponding to both, sebacate and terephthalate‐rich phases were still observable in second calorimetric heating runs. These copolyesters were associated with interesting thermal and mechanical properties. The melting points of all samples were higher than 118°C and the puncture resistance and tensile strength of GL, the tear strength of TME, and the Young's modulus of all samples have been improved. Enzymatic degradability was assessed and the effect of composition and crystallinity on the degradation rate was investigated. The copolyester adding GL appears as a highly promising biodegradable material since it showed a significant weight loss during exposure to all selected degradation media, but also exhibited good performance and properties that were comparable to those characteristic of polyethylene. In brief, the improvement of PBSeT's puncture resistance, tear strength, and degradation performance is extremely important for the development and promotion of degradable foam, film, and elastomer materials. Abstract :